Unlocking the therapeutic potential of Agapanthus Africanus (L.) Hoffmanns: A systematic review of a salt-tolerant medicinal plant with potential healing properties. - Singh, Karishma; Singh, Karishma (Student's Journal of Health Research Africa, 2025)
Introduction Agapanthus africanus, commonly known as the African Lily, is a salt-tolerant plant native to South Africa’s coastal regions and has long been used in traditional African medicine for treating various ailments. This review aims to synthesize current ethnobotanical and scientific knowledge on A. africanus, focusing on its traditional uses, phytochemical composition, pharmacological potential, salt stress tolerance, and ecological adaptability. Methods A systematic literature search was conducted using Scopus, Web of Science, Google Scholar, and other academic databases. The search was limited to English-language publications from the past decade. A total of 82 records were identified, of which 63 studies met the inclusion criteria for quality and relevance. Results The plant is traditionally used to manage pregnancy-related conditions, respiratory issues, infections, and inflammatory diseases. Phytochemical analysis reveals bioactive compounds such as saponins, flavonoids, and anthocyanins, which contribute to its antifungal, antibacterial, anti-inflammatory, and CNS-modulating properties. Emerging evidence suggests additional roles in managing hypertension and depression through ACE and serotonin reuptake inhibition. Conservation concerns are rising due to habitat degradation; although not formally assessed by the IUCN, some subspecies are locally protected in South Africa. Conclusion With its therapeutic potential and natural adaptation to saline environments, A. africanus presents a promising candidate for eco-friendly pharmaceutical development and sustainable agriculture. Realizing this potential requires interdisciplinary research integrating ecology, pharmacology, horticulture, and indigenous knowledge systems to support both conservation and utilization. Recommendations Future research should prioritize the development of standardized extraction techniques and dosing guidelines to enhance repeatability and facilitate the clinical translation of these findings. In vivo and clinical trials will be conducted to validate the pharmacological claims that are now supported by in vitro and ethnobotanical evidence. Ecological monitoring and conservation assessments, with a focus on habitat fragmentation and the implications of climate change.